UPLC/MS–MS assay development for estimation of mozavaptan in plasma and its pharmacokinetic study in rats. (July 2018) - Ezzeldin, Essam; Mostafa, Gamal AE; Iqbal, Muzaffar; Al-Rashood, Khalid A; Asiri, Yousef; El-Nahhas, Toqa
Aim: Mozavaptan is a nonpeptide vasopressin receptor antagonist approved for the treatment of ectopic antidiuretic hormone secretion syndrome.Methods & results: A simple, rapid and fully validated UPLC/MS–MS method was developed for the quantitation of mozavaptan in rat plasma. The chromatographic separation was conducted on an Acquity UPLC BEH™ C18 column with an optimum mobile phase of 10 mM ammonium acetate buffer and 0.1% formic acid in acetonitrile (30:70 v/v) at a flow rate of 0.3 ml/min. The multiple reaction monitoring transitions were performed at m/z 428.16→119.03 for mozavaptan and m/z 237.06→179.10 for carbamazepine (internal standard).Conclusion: The method was effectively applied for the determination of mozavaptan pharmacokinetic parameters after the oral administration of 3 mg/kg mozavaptan in rats.